Development of Graphical Interface System for Inverted Pendulum Stabilization - Susanto, Erwin (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2019)
Currently, most of basic control engineering lectures teach both mathematic model and control of an inverted pendulum to explain stability problems in dynamic systems. The inverted pendulum system is a pendulum controlled with a certain force in order to stand in balance around vertical equilibrium line. Hence this system is a highly unstable system and needs stabilization methods using a  kind of controller. This paper describes how to design a Proportional Derivative Integral (PID) controller via root locus technique to stabilize it and realization of its interface system for monitoring angle trajectory. This visualization is needed to observe the stability and  effectiveness of its mathematic model and control design. Experimental results and analysis show that control design and interface system can be implemented well.